Development of Project Based Learning (PjBL) E-LKPD Assisted by Liveworksheets Application on Statistics Material - Zainal, Hardhani Mardiana; Ramadoni, Ramadoni; Mardiyah, Ainil (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2024)
This research is motivated by the lack of use of electronic media or digital teaching materials in the learning process and students who have difficulty solving problems related to statistics material at SMAN X in Padang. The purpose of this study was to develop a project-based E-LKPD assisted by the application of liveworksheets on statistical material for class X SMAN X in Padang which is valid and practical. This type of research is development using R&D with a plomp development model. The stages used in this development model only reached stage 2, namely the prototyping phase which concurrently tested the validity and one-on-one tests which were useful for seeing the practicality of the E-LKPD by teachers, small group test questionnaires which were useful for seeing the practicality of E-LKPD by students and interview guidelines. Based on the validator's assessment, the results of the validity of the E-LKPD assisted by the liveworksheets application were 91% with a very valid category. The results of practicality with the teacher obtained a final score of 96% in the very practical category. The results of the one-on-one practical test obtained a final score of 92% in the very practical category. The results of the small group practicality test obtained a final score of 88% in the very practical category. Based on the results of the study it can be concluded that the E-LKPD assisted by the liveworksheets application on statistics material at SMAN X in Padang is stated to be valid and practical for use by teachers and students.